Is accounting the English language of business? The role of language in IFRS adoption and information loss - Guan, Jenny Xinjiao; Shafron, Emily; Ye, Kangtao; Zhuang, Wenzi (Review of Accounting Studies, 2025)
Abstract We examine whether and how language barriers influence a country’s decision to adopt International Financial Reporting Standards (IFRS). Our findings reveal that as the distance between a country’s official language and English (i.e., linguistic distance) increases, the likelihood and speed of a country adopting IFRS decrease. Our evidence is consistent with the notion that language barriers impose significant information costs on preparers and users of financial reporting, making IFRS costlier to adopt for countries with severe language barriers. In further analysis, we find that such information costs materialize when these countries eventually adopt IFRS. Specifically, firms in countries with the most severe language barriers experience a worsened post-adoption information environment, as evidenced by increased analyst forecast errors and widened bid-ask spreads. Overall our study suggests that language barriers impede achievement of international accounting harmonization by increasing the costs associated with adopting, understanding, and applying IFRS.